2017
DOI: 10.1007/978-3-319-67262-5_3
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Survey of Lightweight Virtualization Techniques

Abstract: The increasing prevalence of the microservice paradigm creates a new demand for low-overhead virtualization techniques. Complementing containerization, unikernels are emerging as alternative approaches. With both techniques undergoing rapid improvements, the current landscape of lightweight virtualization approaches presents a confusing scenery, complicating the task of choosing a suited technology for an intended purpose. This work provides a comprehensive performance comparison covering containers, unikernel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…While the survey has shown that many practitioners actually build serverless user-facing applications, many of our interviewees were not convinced about this particular use case. An often-voiced concern was that the response time and latency of functions (with a tail latency in the range of multiple seconds [20], when a new container instance is started by the provider) does not lend itself to usage directly in an end user facing request cycle. These interviewees have argued that the primary use case for FaaS should be in backend applications, such as for transforming images, processing logs or telemetry data, scheduling and executing backups, sending out notification emails, and similar tasks.…”
Section: Types Of Serverless Applicationsmentioning
confidence: 99%
“…While the survey has shown that many practitioners actually build serverless user-facing applications, many of our interviewees were not convinced about this particular use case. An often-voiced concern was that the response time and latency of functions (with a tail latency in the range of multiple seconds [20], when a new container instance is started by the provider) does not lend itself to usage directly in an end user facing request cycle. These interviewees have argued that the primary use case for FaaS should be in backend applications, such as for transforming images, processing logs or telemetry data, scheduling and executing backups, sending out notification emails, and similar tasks.…”
Section: Types Of Serverless Applicationsmentioning
confidence: 99%
“…Various Middleware Frameworks of Containers [21] Programming Sensors and IoT Devices (Small VMs Supported by Python Runtime Environments such as Spring and NodeJS) [22][23][24][25] Application Efficiency (Resource Virtualization Technology for Hardware Flexibility) [26] Lightweight Virtualization Solution [27] Virtualization Application to Lower Overhead [28] Definition of Container [29] Strengths of Containers, Lightening Up [30] The Connection between Lightweight Virtualization and Microservice [31] Strategies to Strengthen The Fuzzy Distribution of Microphone Services [32] Cluster Intelligence-Based Strategies [33] Reinforcement…”
Section: Cloud Computingmentioning
confidence: 99%
“…Unikernel is a specialized ultra-lightweight virtualization technique that allows the creation of a single address space machine image using library OS. It allows the creation of OS with the minimal set of OS constructs or libraries, as required by the applications, thus having a very small footprint [29]. Therefore, unikernel is ultra-lightweight and provides higher security and deployment efficiency as compared to VMs and containers.…”
Section: ) Lightweight Virtualizationmentioning
confidence: 99%